Vulnerability assessment of drinking groundwater of buchak-kaniv aquifer under the conditions of quality composition long-term transformation - Levoniuk, Serhii; Udalov, Ihor (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Problems Statement and Purpose. This article is a continuation of the authors’ previous publications on improving the methodical approach to assessing the vulnerability (protection) of drinking groundwater within the Dnipro-Donetsk artesian basin (DDAB) and is a practical component of these studies. In order to find and develop optimal forms of ecological safety management of drinking water supply for the region population, the authors’ improved approach to assessing the vulnerability (protection) of drinking groundwater in the strategically important waters of buchak-kaniv aquifer (BKA) was tested. The purpose of article is the ecological and hydrogeological zoning of research area according to the danger of quality transformation of BKA groundwaters and the determination of zones of increased ecological danger of these waters quality reduction due to elements of surface and deep genesis. Data & Methods. The research is based on the analysis of results of drilling more than 950 wells in this region, as well as about 500 measurements of piezometric levels of BKA and the first interlayer aquifer during 1960-2020. Results. Complex systems of ecological and hydrogeological zoning of the territory of DDAB central part have been developed according to the degree of ecological danger of lowering the quality of BKA drinking groundwater. Zoning of the territory was carried out according to the danger of deterioration of these waters quality by man-made pollutants that enter the waters in the process of downward vertical filtration and migration from the earth surface. Ecologically dangerous areas with a potential decrease in the quality of BKA drinking groundwater due to elements of surface genesis (water intakes of Poltava, Lubny, Myrhorod, Velyka Bagachka, Krasnograd cities and some others) have been identified. Zoning of the territory was carried out according to the danger of deterioration of the BKA groundwater quality due to the upward migration of natural deep substandard waters. Ecologically dangerous areas with a potential decrease in groundwater quality due to elements of deep genesis (water intakes of Poltava, Romodan, Myrhorod, Shyshaky, Opishnia, Gadyach, Krasnograd, Karlivka cities and some others) have been identified. It is recommended to develop measures to increase the ecological safety of the population’s drinking water supply: hydrogeochemical monitoring of characteristic indicators of water quality composition and optimization of the powerful water intakes operating modes (within ecologically dangerous territories); creation of new water intakes (within ecologically safe territories).